Good Governance: The Conceptual and Contextual Perspectives - Emeh Ikechukwu Eke Jeffrey; Ugwuibe Onyemaechi Christopher; Olise Charles Nnamdi (Acta Universitatis Danubius: Administratio, 2019)
A discourse on good governance at any level requires a clear understanding of the concept as one may erroneously assume that everyone understands what good governance means. Thus, this paper not only evaluates the definitions of the concept of good governance, but also contextualized it within the perspectives of what constitutes public interest, the leader’s idiosyncrasy; political party ideologies and the expectations of donor agencies. The study is qualitative and as such its data were documentary and the content analysis approach was used to analyze the data. Anchored on the good governance theory and the cultural theory of governance, this paper found that while good governance has been variously conceptualized, it has not been contextualized in the Nigerian milieu and that the concept serves as a measurement scale in the hands of donor agencies for the evaluation of their performances as tied to their operational objectives in the developing and less developed nations. The study recommended among others that Nigerian political leaders should leverage on the donor agencies’ idea of governance to deliver development to their people and also evaluate their performance while the political parties should reinvent political party ideologies that reflect current realities for the resolution of the myriad societal ills bedeviling Nigeria.